G122(P) Intravenous or oral antibiotics for urinary tract infection/pyelonephritis in children? Development of the melbourne rupert score. (May 2019) - Scanlan, BT; Ibrahim, LF; Hopper, SM; McNab, S; Donath, S; Babl, FE; Davidson, A; Bryant, PA
Abstract : Aims: Using intravenous (IV) antibiotics to treat urinary tract infection (UTI)/pyelonephritis places a significant burden on patients, their families and health care resources. Despite a recent Cochrane review, guidelines do not clearly state the criteria for IV antibiotics in children with UTI/pyelonephritis. We aim to derive and validate a clinical score that incorporates clinical features and patients complexities to guide the decision on the route of antibiotics. Methods: This was an observational study (May 2016 – March 2018) of all children (3m-18y) diagnosed in ED with UTI/pyelonephritis and subsequently confirmed on urine culture. To derive the score, only those aged 12m-12y were included who meet criteria from a recent systematic review. Patients were divided into two groups using the pre-determined gold standard for the 'true' need for IV antibiotics, which was based on the evidence from the Cochrane review and route of antibiotic at 24 hours. Features which were significantly different between the groups were identified. Various combinations of these differentiating features were used to generate receiver operating characteristics (ROC) curves, table 1 . To validate this score, children aged 3m-18y were included. Results: 1237 patients had a confirmed UTI/pyelonephritis: 833 (67%) aged 12m-12y, 271 (22%) aged 3–12 m and 133 (11%) aged 12–18y. Of those aged 12m-12y, 335 (27%) met the definition for inclusion, half of which were used to derive the RUPERT score (Rigor, Urological abnormality, Pyrexia/fever (≥38°C), Emesis/vomiting, Recurrent (>2) UTI, Tachycardia – one point each – maximum of 6 points), area under curve (AUC) of 0.81. A cut-off score of ≥4 to commence IV antibiotics would result in correct classification of 80% of patients (sensitivity 29% and specificity 95%). This score was then validated on a separate cohort and maintained an AUC of 0.81 (sensitivity 50% and specificity 90%). Conclusion: This score can aid clinicians in deciding an appropriate route of antibiotics for UTI/pyelonephritis in children aged 12m-18y.